2010
DOI: 10.1111/j.2042-3306.2010.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and electrolyte balance in horses during an endurance season

Abstract: SummaryReasons for performing study: Limited information exists about the physiological training-induced changes in electrolyte balance of horses competing in long distance endurance races. Objectives: To determine the effects of endurance training and racing on hydration and electrolyte balance in horses. Methods: Blood and urine were sampled at rest in 8 endurance horses before training and after two 11 week training periods (T1 and T2). Each training was followed by a 120 km endurance ride and horses were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
3
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
2
36
3
6
Order By: Relevance
“…By contrast, endurance-trained horses have lower resting RBC, PCV and HB than sprinttrained horses Robert et al, 2010;Trigo et al, 2010). In fact, in our experience, is very common to find PCV as low as 30-32% in endurance healthy horses with good performance .…”
Section: Trainingmentioning
confidence: 79%
See 1 more Smart Citation
“…By contrast, endurance-trained horses have lower resting RBC, PCV and HB than sprinttrained horses Robert et al, 2010;Trigo et al, 2010). In fact, in our experience, is very common to find PCV as low as 30-32% in endurance healthy horses with good performance .…”
Section: Trainingmentioning
confidence: 79%
“…There are two main reasons to explain these results. Firstly, it has been indicated that feeding fibrous diets might increase water consumption and then plasma volume (Robert et al, 2010). The second reason is the effect of a greater release of aldosterone, which promotes water and electrolyte-conserving mechanisms in the kidneys and gastrointestinal tract (McKeever et al, 2002).…”
Section: Trainingmentioning
confidence: 99%
“…As published by Robert et al (2010), studies on endurance and prolonged exercising horses often report only descriptive results, and physiological explanation of changes responsible for the observed alterations is rarely provided. It is probably due to the alterations of plasma volume which vary in horses subjected to the different physical performance on a variety of environmental conditions, as reviewed by Carlson (1987).…”
mentioning
confidence: 99%
“…The decrease was also observed in horses finalists in 120 km-competitions (Robert et al, 2010;Viu et al, 2010). When associating the value found for the chloride ion with pH, it was possible to observe that the initial changes would induce hypochloremic metabolic alkalosis, if the animals continued the route, and showed complications in exhaustion syndrome.…”
Section: Relationship Between Anion Gap and Bicarbonatementioning
confidence: 82%
“…A diminuição também foi observada em equinos finalistas em competições de 120km (Robert et al 2010, Viu et al 2010. Sobretudo, quando associado o valor encontrado para o íon cloro juntamente com o pH, foi possível entender que as alterações iniciais estariam induzindo alcalose metabólica hipoclorêmica, caso os animais continuassem o percurso, e ainda complicações relevantes na síndrome de exaustão.…”
Section: Concentração Total Do íOn Clorounclassified